Association between rectal douching and HIV and other sexually transmitted infections among men who have sex with men: a systematic review and meta-analysis. (9th May 2019) - Li, Peiyang; Yuan, Tanwei; Fitzpatrick, Thomas; Smith, Kumi; Zhao, Jin; Wu, Guohui; Ouyang, Lin; Wang, Ying; Zhang, Kechun; Zhou, Yiguo; Li, Meijuan; Chen, Dahui; et al.
Abstract : Background: Men who have sex with men (MSM) are disproportionately affected by HIV and other STIs worldwide. Rectal douching, which is commonly used by MSM in preparation for anal sex, may increase the risk of HIV and other STIs by injuring the rectal mucosa. Results from individual studies reporting associations between rectal douching and HIV and other STIs among MSM are inconsistent. We performed a systematic review and meta-analysis to estimate the association between rectal douching and HIV and other STIs among MSM. Methods: We searched PubMed, Embase, Scopus and Web of Science for studies published from January 1970 to November 2018. Studies that reported ORs and 95% CIs of associations between rectal douching and infection with HIV/STIs, or reported enough data to calculate these estimates, were included. We assessed risk of bias using the Newcastle-Ottawa Scale. ORs were pooled using a random effects model. Results: Twenty-eight eligible studies were identified in our review, of which 24 (20 398 participants) were included in the meta-analysis. Rectal douching was associated with increased odds of infection with HIV (OR 2.80, 95% CI 2.32 to 3.39), and any STI other than HIV (including hepatitis B virus (HBV), hepatitis C virus (HCV), chlamydia, gonorrhoea, syphilis and human papillomavirus) (OR 2.46, 95% CI 1.95 to 3.11) among MSM. For specific STIs, douching was associated with increased odds of viral hepatitis (HBV, HCV) (OR 3.29, 95% CI 2.79 to 3.87), and chlamydia or gonorrhoea (OR 3.25, 95% CI 2.02 to 5.23). These associations remained significant in studies that adjusted for potential confounders. Conclusion: Rectal douching may put MSM at increased risk for infection with HIV and other STIs. Longitudinal studies are needed to clarify this association, and health education materials should inform men of the potential for increased risk of infection with rectal douching.